Strategi Peningkatan Pelayanan Light Rail Transit Dalam Integrasi Antar Moda Mewujudkan Transportasi Berkelanjutan - Wahyuni, Endah; AR, Hasmawaty, (SEIKO : Journal of Management & Business, 2023)
This research aims to identify problems and find solutions that can improve the progress of the South Sumatra LRT fast train. By using the SWOT analysis method, we identified the strengths, weaknesses, opportunities and threats facing the South Sumatra LRT. This research method involves collecting primary data through interviews, questionnaires, observations and documentation from South Sumatra LRT employees and high-speed train passengers. The research population included 86 internal employees and 100 external passengers. We used nonprobability sampling techniques with 65 respondents. Data was analyzed using qualitative and quantitative approaches. The research results show that the South Sumatra LRT has made progress in improving the quality of its services. Alternative strategies identified through SWOT analysis involve utilizing competent human resources, maximizing existing infrastructure, utilizing LRT routes more effectively, and needing to improve system management to achieve the set targets. This strategy is expected to help overcome challenges and maximize the potential of the South Sumatra LRT fast train to achieve sustainable transportation. Kata Kunci: light rail transit, transportasi berkelanjutan.